Financial Development, Economic Growth, and Environmental Degradation Nexus in ASIAN Emerging Markets - Intan Dana Lestari; Nury Effendi; Anhar Fauzan Priyono (Jurnal Ekonomi Pembangunan, 2020)
Environmental degradation is one of the major problems in the world recently and one of the United Nations’ (UN) sustainable development goals (SDGs). Emerging markets countries that have become major players in the global economy and the main source of world economic growth have great potential to contribute the environmental degradation due to increased economic activities. This paper investigates the impact of financial development and economic growth on environmental degradation in Asian emerging markets. A panel environmental degradation model using financial development from banking sector and capital market sector, economic growth, Foreign Direct Investment (FDI), and urbanization variables that are major determinants of CO2 emission as a proxy of environmental degradation. The periods considered were 1980 – 2018 for banking model, and 1996 – 2018 for financial sector model (banking sector and capital market sector). A panel data approach applied such as cross-section dependence, panel unit root, panel cointegration, Fully Modified OLS (FMOLS) and Dynamic Ordinary Least Square (DOLS). The empirical finding revealed that in Asian emerging markets there is positively long-term relationship between financial development from banking model with environmental degradation. Nevertheless, we do not find any long-term relationship between financial development from financial sector model with environmental degradation. Moreover, the quadratic negative signed for economic growth showed the existence of Environmental Kuznets Curve (EKC).